EFEKTIVITAS TERAPI EMOTIONAL FREEDOM TECHNIQUE (EFT) TERHADAP KECEMASAN PASIEN KANKER PAYUDARA STADIUM II DAN III - Ningsih, Santi Fitria; Karim, Darwin '; Sabrian, Febriana ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The aim of this study wasÂ to determine the effectiveness of Emotional Freedom Technique (EFT) therapy to anxiety of breast cancer stage II and IIIÂ patients . This study used